"Life Goes On." Everyday Tasks, Coping Self-Efficacy, and Independence: Exploring Older Adults' Recovery From Hip Fracture. (July 2018) - Langford, Dolores; Edwards, Nicola; Gray, Samantha M.; Fleig, Lena; Ashe, Maureen C.
Older adults face many challenges in the first few months after hip fracture. Rehabilitation holds promise to assist the recovery process. Therefore, we used semistructured interviews to explore older adults' and allied health professionals' acceptance of a rehabilitation intervention for hip fracture, and we described perceptions of the early recovery period (<4 months). Interviews were recorded and transcribed verbatim; three authors independently read the transcripts multiple times and together developed themes guided by Interpretive Description. Older adults described the intervention as acceptable and provided valuable feedback for its future implementation. Older adults also provided reflections on their experience of fracture recovery. Themes that emerged included physical limitations and loss of independence, the long recovery time, and coping with additional complications of living with multimorbidity. To overcome challenges, older adults identified the need for social support and physical activity, balanced by their own personal outlook.